Don't Worry, Be Right! Survey Wording Effects on In flation Perceptions and Expectations - Lena Dräger; Ulrich Fritsche (Hamburg University, Department Socioeconomics, 2013)
We compare the formation of quantitative infl ation perceptions and expectations from questions asked either in terms of price changes or in terms of the in flation rate in a new socio-economic household survey established at the University of Hamburg. In addition to socio-demographic characteristics, we evaluate effects of happiness, trust in people and the central bank, risk attitudes as well as news heard on monetary policy or in flation. We find that the upwards bias of reported perceptions and expectations is higher under the price wording and responses are more heterogeneous, but non-response rates are higher in the infl ation wording. Generally, consumers have lower perceptions or expectations with a higher level of education, which also significantly lowers the probability of non-response. Consumers that perceived positive news on monetary policy or infl ation also tend to give lower infl ation estimates and vice versa. Additionally, our results suggest that happier individuals have significantly lower perceptions and expectations under the price wording, while more risk-averse consumers give significantly higher in flation estimates under the inflation wording.
Keywords: E31; D84; C83; 330; in flation perceptions; in flation expectations; survey design; mental representations; economic beliefs